Pengaturan Keselamatan dan Keamanan Pelayaran di Perairan Indonesia - A. A. ayu Diah Uthari Pramesti; I Ketut Kasta Arya Wijaya; Desak Gde Arini (Warmadewa Press, 2021)
Indonesia is a maritime country surrounded by a sea that is rich in natural resources, therefore a unified system is needed to maintain security and also to allocate all energy sources offered by the sea so that it can be managed appropriately. The management of water safety and security in Indonesia is regulated in Law Number 17 of 2008 concerning Shipping. In this research, there are two main problems that will be examined, namely first about the management arrangements for safety and security requirements in Indonesian maritime territory and second What is the authority of the local government in developing the safety and security requirements of shipping in Indonesian maritime territory. This research is a normative legal research, using a statutory approach and a conceptual approach. The result of this research is the management of shipping coaching is carried out by the government. The form of guidance carried out by the government is in the form of supervision, control and regulation. Legal protection for the administration of regional autonomy is in line with the provisions of Law Number 23 o/2014 which involves regional governments and carries out legal protection for various government affairs in the context of community service and natural resource management.